Provision of adolescent and youth-friendly services in public health facilities in Migori County, Kenya - Nyaga, Lillian N.; Ongombe, Musa O.; Mwangi, Eunice M. (International Journal Of Community Medicine And Public Health, 2023)
Background: Global and national guidelines on provision of adolescent and youth-friendly services (AYFS) exist. However, the extent to which these services are provided in developing countries, including Kenya, is unknown. Therefore, this study aimed to assess provision of AYFS in public health facilities in Migori County, Kenya. Methods: A cross-sectional study design was employed. The study setting was public health facilities in Migori County. The county has 275 health facilities, of these 159 are government owned/public health facilities. A multistage sampling of 114 public health facilities was done from which 210 healthcare providers (HCPs) were sampled using simple random sampling. Three facility in-charges were purposively selected to represent each of the county's three Levels of healthcare delivery system. Data was collected using structured questionnaires, key informant interviews guide, and Health facility observation checklists. Results: Majority 153 (74%) practiced nursing and 148 (71%) had worked at their current workstation between 1-5 years. Equitable, accessible, acceptable, appropriate, and effective AYFS are provided in the government owned public health facilities. Conclusion: Inadequate AYFS training of healthcare providers and poor implementation of existing policies including weak engagement of young people in AYFS significantly hinder the effective provision of AYFS in public health facilities.